STOP SPREADING RUMOURS ON POISONOUS PLANT CLAIM – LODGE OFFICIAL COMPLAINT FOR USM TO CARRY OUT IMMEDIATE INVESTIGATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
We have received numerous inquiries regarding the news that went viral on social media about a poisonous plant that allegedly killed a Universiti Sains Malaysia (USM) student conducting research on the plant.